Dangerous Goods Transportation by Road: a Risk Analysis Model and a Global Integrated Information System to Monitor Hazardous Materials Land Transportation in Order to Protect Territory - M. Orso Giacone; F. Bratta; P. Gandini; L. Studer (Chemical Engineering Transactions, 2012)
DESTINATION project, started in 2010 in the framework of the Italy/Switzerland Operational Program for Transfrontier Co-operation 2007-2013, was born to answer to the increasing needs of public bodies to share data on hazardous material land transportation and to develop instruments and methodologies to ensure territorial and environmental protection. The partnership is made of 5 members: Canton Ticino, Piedmont Region as Leader of the project, Lombardy Region, Autonomous Region of Aosta Valley and Autonomous Province of Bolzano Alto Adige. Technical partners working on DESTINATION are CSI Piemonte, 5T S.r.l. and Laboratorio Mobilità e Trasporti del Politecnico di Milano. One of the main objective of the project is the definition of a risk analysis model of the land transportation of hazardous materials, able to take into account even environmental vulnerabilities. It will constitute the basis to a new information system design called GIIS (Global Integrated Information System), in order to contribute to road accident prevention, real-time monitoring of Dangerous Goods Transportation by road (DGT) through On Board Units and fixed points (gates) and more efficient emergency management. In this paper we describe the DGT risk model designed and the main features of the Information System that is going to be developed.